The effectiveness of jet impingement cooling system on the pressure side of the turbine blade - Megavarnan Mahivanan, 1994- , author; Mohamad Nor Musa, supervisor 634310; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2017